1995
DOI: 10.1145/210126.210127
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for reducing consistency-related communication in distributed shared-memory systems

Abstract: Distributed shared memory (DSM) is an abstraction of shared memory on a distributed-memory machine. Hardware DSM systems support this abstraction at the architecture level; software DSM systems support the abstraction within the runtime system. One of the key problems in building an efficient software DSM system is to reduce the amount of communication needed to keep the distributed memories consistent. In this article we present four techniques for doing so: software release consistency; multiple consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 12 publications
0
75
0
2
Order By: Relevance
“…Munin [8] and SAM [33] are object-based DSMs with supports to optimize some object access patterns. However, they require the programmer to explicitly annotate the object with some pattern declaration.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Munin [8] and SAM [33] are object-based DSMs with supports to optimize some object access patterns. However, they require the programmer to explicitly annotate the object with some pattern declaration.…”
Section: Related Workmentioning
confidence: 99%
“…There are also choices for the coherence operations, such as that between a multiple-writer protocol or a single-writer protocol. The multiple-writer protocol introduced in Munin [8] supports concurrent writes on different copies using the diff techniques. It may however incur heavy diff overhead compared with conventional single-writer protocol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation of the modifications can be delayed until the next synchronization point. Many projects such as TreadMarks [1] or Munin [3] have shown that the use of a relaxed consistency software DSM along with some consistency control on synchronizations can avoid the cost of maintaining the memory consistency during the execution of a parallel loop.…”
Section: Introductionmentioning
confidence: 99%
“…When a write access is performed on a write-protected page, a protection violation interrupt will occur. The interrupt handler in the DSM system can be extended to record the modified page's identifier in the corresponding view, as well as making a twin of the accessed page in the multiple-writer scheme or obtaining the ownership of the accessed page in the single-writer scheme [5].…”
Section: When a Write Access Is Performed On An Invalidatedmentioning
confidence: 99%